Consumption of Myrtillocactus geometrizans by Frugivorous Bats of the genus Sturnira in a Tropical Deciduous Forest in the Bajío, Guanajuato, Mexico: Myrtillocactus, a new resource for Sturnira - González-Torres, Oscar Francisco; Vásquez-Cruz, Marilyn; García Méndez, Antonio (Therya Notes, 2026)
Frugivory interactions are essential in tropical ecosystems due to their impact on forest regeneration through seed dispersal. Frugivorous bats play a key role in these interactions because of their ability to travel long distances and consume a wide variety of fruits. This study assessed the diet of frugivorous bats in a tropical deciduous forest (TDF). Bats were captured over an annual cycle from May 2023 to March 2024, covering both the rainy and dry seasons. Four mist nets were set among the vegetation and in natural roosts from 18:00 to 01:00 hours. Captured bats were placed in cloth bags to obtain fecal samples. With a sampling effort of 5760 m/net/night, 35 bats from the families Phyllostomidae, Vespertilionidae, and Molossidae were recorded. Sturnira hondurensis was the most abundant species. Two genera of plants, Solanum and Myrtillocactus, were identified from fecal samples of captured individuals. The presence of garambullo (Myrtillocactus geometrizans) in the diet of S. hondurensis and S. parvidens is reported for the first time. The results suggest that the diet of these bats is composed mainly of Solanum ferrugineum fruits, supplemented with M. geometrizans, reflecting a sequential use of food resources according to plant phenology.